INCLUSIVISM OF RELIGIOUS EDUCATION TEACHERS IN INDONESIA - Hayadin, Hayadin; Mastiyah, Iyoh; Muntafa, Farhan; zada, Hamami (Balai Penelitian dan Pengembangan Agama Semarang, 2019)
The research aimed to measure the level of inclusiveness of religious education teachers in Indonesia in 2018. The research method was a survey, conducted thorough capital cities in 34 provinces. The respondents were religious education teachers from Moslem, Christian, Catholic, Hinduism, and Buddhism at the secondary school level. The total sample was 3675 from 7976 population in the whole province capitals. They were selected based on Proportional Random Sampling technique and used Yamane formula at the level of confidence at 95 percent. The instrument research was the questionnaire of religious understanding which was constructed from three dimensions of variables, namely religious understanding toward the relation of religion and state, the relation among different religions and the relationship within the same religion. The research data technique analysis used structural equation modeling. The result showed that the inclusiveness level of religious education teachers iwas at 76,55, which was higher than the cut off value which was at 75,0. It means that the religious understanding of religious education teachers was good or generally at an inclusivism level.